2018
DOI: 10.1029/2017jd027998
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Inertia Gravity Waves in the Lower Stratosphere Over the Arctic Region Based on Radiosonde Observations

Abstract: Relative to many investigations of inertial gravity waves (IGWs) in the Antarctic, IGW activity in the Arctic region was paid less attention to. We use radiosonde observations at the Ny‐Alesund station (78.9°N, 11.9°E) from April 2012 to June 2016 to study the IGW characteristics in the lower stratosphere over the Arctic. The observation reveals a prevailing eastward zonal background wind below 20 km and an obvious annual cycle of the background temperature from the troposphere to the lower stratosphere, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 89 publications
(237 reference statements)
0
30
0
Order By: Relevance
“…Whether in the troposphere or stratosphere, the disturbance components of the zonal wind and meridional wind rotate clockwise with height, representing the upward propagation of energy (the energy propagation direction is used to represent the vertical propagation direction of GWs). The horizontal wind and temperature disturbance rotate clockwise with the height, indicating that the actual propagation direction is consistent with the azimuth angle of the major axis (Huang, 2018). The horizontal propagation directions of GW in the troposphere (2–14 km) and stratosphere (18–28 km) are 58.8° and 49.5°, respectively.…”
Section: Extraction Of Quasi‐monochromatic Igwsmentioning
confidence: 79%
“…Whether in the troposphere or stratosphere, the disturbance components of the zonal wind and meridional wind rotate clockwise with height, representing the upward propagation of energy (the energy propagation direction is used to represent the vertical propagation direction of GWs). The horizontal wind and temperature disturbance rotate clockwise with the height, indicating that the actual propagation direction is consistent with the azimuth angle of the major axis (Huang, 2018). The horizontal propagation directions of GW in the troposphere (2–14 km) and stratosphere (18–28 km) are 58.8° and 49.5°, respectively.…”
Section: Extraction Of Quasi‐monochromatic Igwsmentioning
confidence: 79%
“…The IGWs in the MLT over Andes evidently exhibit the preferential propagation in the meridian direction relative to in the zonal direction. The anisotropy in the wave propagation direction is extensively reported at different latitudes (Hu et al., 2002; Huang et al., 2018; Moffat‐Griffin et al., 2011; Vincent & Alexander, 2000; Yamamori & Sato, 2006; Yoshiki et al., 2004), which is generally attributed to the wave excitation process and propagation effect.…”
Section: Igw Analysismentioning
confidence: 94%
“…The frequency spectra in the zonal and meridional winds have the PSD slope between −1.5 and −2.2 in radar (Hoffmann et al., 2010; Larsen et al., 1986; Y. Yamamoto et al., 1996) and lidar (Senft & Gardner, 1991; Yang et al., 2006) data. A lot of observations showed that the index ranges of frequency and vertical wavenumber spectra in the temperature fluctuations are approximately the same as those in the horizontal wind perturbations (Chen et al., 2016; Cot, 2001; Guharay & Sekar, 2011; Guo et al., 2017; Huang et al., 2018; Wu et al., 2006; Yang et al., 2010). It can be noted that the observed frequency (vertical wavenumber) spectrum slope exhibits a change around the canonical value of −5/3 (−3) derived from the spectral theories.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations